A produção de conhecimento em gênero e sexualidade no ensino de biologia no Brasil: uma revisão sistemática, 1996-2022 - Maia, Marcos Felipe Gonçalves (2023)
This dissertation in education deals with the concepts of gender and sexuality in Biology teaching in Brazil. Based on a systematic literature review aiming to map and analyze the production of knowledge on these topics in Biology Teaching in the country from 1996, year of the approval of the National Education Law, to 2022, it imagines new possibilities of research and dialogue. A search was conducted in the following databases, using the terms “gender, sexuality, biology teaching”: Digital Library of Theses and Dissertations (BDTD/IBICT), Google Scholar, Microsoft Academic, CAPES Journal Collection, Web of Science and Scopus. It reached a total of 71 texts of various types: doctoral dissertations, master theses, final papers of undergraduate and specialization programs, journal articles, conference articles, and book chapters. As an initial descriptive-exploratory approach, based on the full reading of the texts, five categories were created: 1) chronology, 2) typology, 3) geographic region, 4) thematic focus and 5) bibliometric indicators. Within the 1996-2022 time frame the first text appeared in 2004. The most frequent type of text was journal article, followed by master thesis, conference paper, doctoral dissertation, specialization final paper, undergraduate final paper, and book chapter, in descending order. The South and Southeast regions together produced 80% of the entire textual mass studied. The thematic focus was subdivided into eight major themes: 1) curriculum, 2) teacher, 3) student, 4) pedagogical practices, 5) school/community relations, 6) body, gender and sexuality, 7) biological knowledge and 8) textbooks. The bibliometric indicators support the argument that the textual mass, although heterogeneous, presents remarkable quality (high ranked journals and programs), impact (frequent citation and few self-citation) and scientific productivity (average of 78 publications for each one of the 113 authors). In a second approach, content analysis was carried out, this time only of texts with an empirical and interventional approach, excluding those with a bibliographic-documentary approach. Thirty-two texts were analyzed and grouped according to the purpose of the research: empirical or interventional. Then, excerpts illustrating the diversity of approaches in gender and sexuality were selected. Of the eight approaches, only the traditional was absent. All the other seven (biological-hygienist, religious, human rights, sexual rights, emancipatory, queer and in-formative-pedagogical) had at least one exemplar text; there was a higher incidence of the emancipatory and sexual rights approaches. At the end, eleven clues are presented to think about possibilities for further research and dialogue: A) not running away from biology, B) broadening the notion of curriculum, C) teacher training, D) overcoming the dichotomy students as objects, teachers as subjects, E) sources of information, F) the use of pleasures, G) what can be defined as pedagogical practices? H) family and community, I) biological knowledge, J) textbooks and K) bibliometric indicators. In conclusion, considering the articulation between the concepts of gender and sexuality in the texts analyzed, it is highlighted that they are complex concepts in the process of cultural representation, and that the biological knowledge versus social/human knowledge dichotomy is unsustainable for teaching purposes, or for Education in Biology. Hence, a call to a Biology of natureculture is in order.